The Relationship Between The Explosive Power Of The Leg Muscles And The Speed And Accuracy Of The A (Straight) Kick In Pencak Silat Athletes - Ayu Rachmawati; Hilmy Aliriad; Nurman Ramadhan (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
The primary objective of this empirical study was to investigate and quantify the correlation between the explosive power of the leg muscles and the velocity of straight kicks among Pencak Silat practitioners affiliated with the Persaudaraan Setia Hati Terate in the Bancar District of Tuban. The study involved a cohort of 20 athletes, representing the entire population of the branch, who were selected through a total sampling (saturated sampling) technique to ensure data integrity. To gather precise physical and technical data, two validated instruments were employed: the vertical jump test, utilized as a metric for lower-body explosive power, and a specialized timed-kick test designed to evaluate the rapid execution of straight kicking maneuvers. The collected data underwent rigorous statistical processing using the Pearson Product Moment correlation formula. The analytical results revealed a calculated r-coefficient of 0.815, which significantly exceeds the critical r-table value of 0.444 at a 5% significance level. Furthermore, the observed significance value (2-tailed) was recorded at 0.000, which is well below the established alpha threshold (α = 0.05). These metrics provide conclusive evidence of a positive, significant, and remarkably strong relationship between the explosive capacity of the leg musculature and the resulting speed of the athlete’s straight kick. Based on these findings, it can be inferred that the explosive power of the lower extremities serves as a critical determinant of kicking performance; as an athlete's power output increases, there is a commensurate and linear improvement in the acceleration and impact speed of their straight kicks. Consequently, this study offers a strategic recommendation for coaching staff: to achieve peak competitive performance, training curricula must prioritize plyometric and explosive strength conditioning. Integrating targeted leg power exercises into regular practice sessions is essential for optimizing the technical efficiency and offensive capabilities of Pencak Silat athletes in competitive settings